UPAYA INDONESIA DALAM MENCEGAH PERDAGANGAN ILEGAL SENJATA API BERKALIBER KECIL DAN RINGAN PADA TAHUN 2006-2008 - Wulandari, Putri Arianingsih Suci; Hanura, Marten; Susitianingsih, Hermini (Journal of International Relations, 2015)
Illicit trafficking of Small Arms and Light Weapons (SALW) is animportant issue as it can be the source of the emerging conflicts andtransnational crimes. Indonesia is one of the destination countries of thiscrime. This issue can be a threat for human rights, security, and thedevelopment of the country. Transnational crime theory, liberalinstitutionalism,and international regime, are used in this research.Those theories explain that cooperation and international regime areneeded by Indonesia to solve the Illicit trafficking of SALW. Therefore,Indonesia has adopted UNPoA as a standard to implement the preventionof Illicit trafficking of SALW’s problem in national, regional, and globallevel. However, in 2007-2008, Illicit trafficking of SALW issue inIndonesia decreased after facing a previous significant increase. Thisresearch aims to know Indonesia’s capability to prevent Illicit traffickingof SALW through UNPoA implementation. Descriptive-Analysis type ofresearch is used to describe the history of Illicit trafficking of SALW inIndonesia, then to analyse Indonesia’s efforts through UNPoA byidentifying the obstacles and the stimulant. The results of this researchshows that Indonesia has been good enough to prevent Illicit traffickingof SALW. However, there had been some factors as geographic,economic, socio-culture, law, and foreign policy, that detained the effortsto prevent Illicit trafficking of SALW.